Status of Coral Health and Disease in Kessilampe Waters, Kendari, South East Sulawesi - Ratna Diyah Palupi; Rahmadani Rahmadani; Ira Ira (Marine Science Department Diponegoro University, 2018)
Diseases of coral reef organisms have become a global threat to coral reefs and a major cause of reef deterioration. The presence of coral diseases influence marine resources productivity that interact with coral reefs. The purpose of this research is to identify coral disease types and prevalence which include coral health compromiser. Data collection was done by using 40 m2 belt transects at three observation stations. The result showed that the White Syndrome (WS), Bleaching, Ulcerative White Spot (UWS), Skeleton Eroding Band (SEB), White Patch (WP), and Non Focal Bleaching were found at research sites, while the coral health compromisers were Sediment damage, fish bite, invertebrate galls, flatworm infestation, and pigmentation response. In addition disease of White Syndrome (WS), Bleaching, and Ulcerative White Spot (UWS) were the main disease with prevalence of disease is approximately 4%, while the others were lower than 1%. Overall the prevalence of diseases (14,52%) is higher than compromise health (13,98%). A total of 186 coral colonies observed with 27 colonies were affected by diseases. Meanwhile, the waters quality (salinity, pH, and nitrate) were below the threshold quality standards for marine aquatic animal and not supported of coral organism was presume organisms against pathogens bacterial. Although the prevalence of coral disease is still in normal condition but the decrease of water quality can lead the risk. Good management is required from local government to improve the water quality especially from terrestrial impact.